Prognostic value of the lactate dehydrogenase to albumin ratio in advanced non-small cell lung cancer patients treated with the first-line PD-1 checkpoint inhibitors combined with chemotherapy - Luo, Meifeng; Wei, Huiting; Qiu, Moqin; Su, Cuiyun; Ning, Ruiling; Zhou, Shaozhang (Frontiers in Immunology, 2025)
BackgroundThis study aimed to investigate the prognostic value of pretreatment lactate dehydrogenase to albumin ratio (LAR) in advanced non-small cell lung cancer (NSCLC) patients treated with first-line programmed cell death protein 1 (PD-1) checkpoint inhibitors and chemotherapy.MethodsA retrospective cohort study was conducted on advanced NSCLC patients treated with first-line PD-1 checkpoint inhibitors plus chemotherapy at Guangxi Medical University Cancer Hospital. The receiver operating characteristic (ROC) analysis determined the optimal LAR cutoff values for prediction. Univariate and multivariate analyses identified independent prognostic factors, and survival curves were estimated using the Kaplan-Meier method. Subgroup analysis evaluated the association between high LAR and disease progression and death risk.ResultsA total of 210 patients were enrolled, with a mean age of 58.56 ± 10.61 years and a male proportion of approximately 79.05%. ROC analysis found the optimal LAR cutoff value was 5.0, resulting in a sensitivity of 78.87% and a specificity of 44.6% (area under the ROC curve 0.622; P = 0.001). Multivariate analysis revealed a significant positive association between LAR and overall survival (OS) after adjusting for confounders (HR = 2.22, 95% CI = 1.25-3.96, P = 0.007). Subgroup analysis confirmed the relationship between high LAR and the risk of disease progression and death across all patient subgroups.ConclusionsPretreatment LAR may be a potential independent prognostic marker for advanced NSCLC patients receiving PD-1 checkpoint inhibitors plus chemotherapy. A large-scale, prospective study is necessary to confirm these findings.